Structure, Antigenic Properties, and Highly Efficient Assembly of PCV4 Capsid Protein - Wang, Dongliang; Mai, Jinhui; Lei, Bo; Zhang, Yingjie; Yang, Yi; Wang, Naidong (Frontiers in Veterinary Science, 2021)
Porcine circovirus type 4 (PCV4), a recently reported circovirus, was first identified in pigs with clinical signs similar to porcine dermatitis nephropathy syndrome (PDNS), in Hunan province, China, in 2019. More knowledge regarding the assembly of capsid protein (Cap) into virus-like particles (VLPs), their structure and antigenic properties, are needed to provide new knowledge for diagnosis and further characterization of PCV4. In this study, high-level expression of PCV4 Cap was achieved in Escherichia coli with purified Cap self-assembling into VLPs (~20 nm) in vitro. Furthermore, these VLPs were internalized in vitro by PK15 and 3D4/21 cell lines. Significant structural differences between PCV4 and PCV2 capsids were demonstrated among loops (loop BC, CD, DE, EF, and GH), based on comparisons of 3D structures. In addition, five potential B cell epitopes identified in silico were mostly located in surface-exposed loops of PCV4 capsid. Cross-reaction between PCV4 and PCV2 or PCV3 conferred by humoral immune responses was deemed unlikely on the basis of ELISA and Western blotting for assessment of VLPs and using PCV4 or PCV2 VLPs. In conclusion, these studies provided new knowledge regarding PCV4 capsid surface patterns. It is noteworthy that the PCV4 VLPs prepared in our study have much potential for development of serological diagnostics for PCV4 and to further characterize this virus.